Wearable non‐invasive blood glucose monitor system based on galvanic skin resistance measurement - Massimo Donelli (Wiley, 2021)
Abstract This work proposes a wearable system for the non‐invasive measurement of the blood glucose level. In particular, the blood glucose variations are related with the skin resistance measured with a suitable sensor. A microcontroller is aimed to measure, store and transmits on a wireless channel, the blood glucose level in a simple, non‐invasive and unsupervised way. The system is particularly useful to monitoring the glucose level in diabetic patients, and to perform the oral glucose tolerance test (OGTT) useful to identify metabolic diseases and to diagnose diabetes mellitus in the early stage. The preliminary obtained results are quite promising and demonstrated the potentialities of the device as diagnostic and home care tool.